Efecto de aplicaciones de silicio sobre el control de piricularia y el rendimiento en arroz (1983)
A tiel experinlent was carried out in 1980 at the Estación Experimental La Libertad, located at Villavicencio, Meta. Three silicate sources were tested at three different levels on three varieties of rice. The silicated sources were rice husk (207- of Si02), ashes rice husk (90% of Si02) and sodium-metasjljcate (98% of Si02). The doses were 0 ppm, 30 ppm, and 80 ppm of Si02. The varieties were Cica 9 susceptible to Pj'ricularia oryzae Cay., Cica 4 with middle resistance to Pt'ricu/aria and Cica 8 with a wide resistance to the disease. These treatments were used in order to observe the effect of silicon on the mechanical resistance to Pvricu/aria, reported by Japanese authors (5, 6, 7, 8, 9, 10, 13, 15, 16). An other objectives of this work to measure the up taking of phosphorus and silicon by the rice crop and to measure the harvest increment as response to the supply to of silicates. The sources and the doses of Si02 showed not differences among them; the varieties presented high significative differences since they have different adaptation to this enviromental conditions; however they did not show response to the treatments. This result was explained on the vasis of the low Si02 levels used, or because the soils of the La Libertad serie do not have deficiency of available silicon.